2018
DOI: 10.1002/ange.201800354
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra‐Robust and Crystalline Redeemable Hydrogen‐Bonded Organic Framework for Synergistic Chemo‐Photodynamic Therapy

Abstract: The low structural stability of hydrogen-bonded organic frameworks (HOFs) is at horny issue retarding the development of HOFs.Arational design approach is now proposed for construction of astable HOF.The resultant HOF (PFC-1) exhibits high surface area of 2122 m 2 g À1 and excellent chemical stability (intact in concentrated HCl for at least 117 days). An ew method of acid-assisted crystalline redemption is used to readily cure the thermal damage to PFC-1. With periodic integration of photoactive pyrene in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(47 citation statements)
references
References 55 publications
2
45
0
Order By: Relevance
“…3 and 4) [5][6][7][12][13][14][15][16] . Although the density of HOF-NF is lower than most modern energetic compounds [38][39][40] , it has one of the highest densities reported for HOFs so far [19][20][21][22][23][24][25][26][27][28] . This is because (1) the pores, which are filled with NF1 and NF2, occupy about 17% of the volume of the unit cell, which is lower than most of the occupancy of pores among reported HOFs; and (2) the introduction of the highly dense NF.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…3 and 4) [5][6][7][12][13][14][15][16] . Although the density of HOF-NF is lower than most modern energetic compounds [38][39][40] , it has one of the highest densities reported for HOFs so far [19][20][21][22][23][24][25][26][27][28] . This is because (1) the pores, which are filled with NF1 and NF2, occupy about 17% of the volume of the unit cell, which is lower than most of the occupancy of pores among reported HOFs; and (2) the introduction of the highly dense NF.…”
Section: Resultsmentioning
confidence: 89%
“…Contrary to MOFs and COFs (covalent organic frameworks), HOFs are easily prepared, their structure can be easily elucidated using single-crystal X-ray diffraction, the starting materials are readily found, and their regeneration processes are low energy-consuming 22,23 . In particular, HOFs show excellent thermal stability [24][25][26][27][28] . For example, HOF-19 23 and HOF-TCBP 24 show thermal stabilities as high as 350 and 395°C (Fig.…”
mentioning
confidence: 99%
“…Pyrene, a classic fused benzene ring molecule with planar conformation and large π-conjugated system, is chosen as the center of the tectons. Previously, 1,3,6,8-tetrakis (p-benzoic acid) pyrene (H 4 TBAPy), has been used to construct a stable HOF, known as PFC-1 11 (we name it as HOF-101 as this material was made prior to the publication of PFC-1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, hydrogen-bonded organic frameworks (HOFs), [1][2][3][4] self-assembled from pre-designed molecular tectons using intermolecular H-bonding interactions, are rapidly expanding into a library of novel functional crystalline porous materials with diverse structures and applications including gas storage and separation, 5,6 chiral separation, 7 chemical sensing, 8 proton conduction, 9 and catalysis. 10,11 However, since the first report of HOF materials with permanent microporosity about a decade ago, 12 the development of HOFs has been hindered due to poor stability as a result of the weak H-bonding nature. Alternatively, various synthetic porous solids such as silicates, 13 carbons, 14 MOFs, 15 and COFs 16 have achieved a wide range of pore sizes from micro-to mesopores.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al reported that biphenyl derivative 9 gave the stable, interpenetrated, 3D-networked framework (HOF-TCBP) with SA (BET) of 2066 m 2 g − 1 [79]. Liu et al constructed the pylene-based HOF (PFC-1) with SA (BET) of 2122 m 2 g − 1 from 10 and demonstrated proof-of-concept for chemo and photodynamic therapy [80]. HOF JLU-SOF-1-R composed of the homochiral 11 had an SA (BET) value of 460 m 2 g − 1 and selective sorption toward CO 2 [81].…”
Section: Networked Structures Connected By Carboxylic Acid Dimersmentioning
confidence: 99%